ChemInform Abstract: Highly Efficient One‐Pot Amination of Carboxylate‐Substituted Nitrogen‐Containing Heteroaryl Chlorides via Staudinger Reaction. Issue 22 (13th May 2013) - Kandalkar, Sachin R.; Kaduskar, Rahul D.; Ramaiah, Parimi Atchuta; Barawkar, Dinesh A.; Bhuniya, Debnath; Deshpande, Anil M.
Abstract Chloropyridines and analogues are converted to the corresponding amino derivatives by azidation followed by Staudinger reaction and subsequent mild acidic hydrolysis.